Metabolomics insights of conventional and organic tempe during in vitro digestion and their antioxidant properties and cytotoxicity in HCT-116 cells - Mio Asni, Nurul Syahidah; Surya, Reggie; Mohmad Misnan, Norazlan; Lim, Seng Joe; Ismail, Norzila; Sarbini, Shahrul Razid; Kamal, Nurkhalida (Elsevier, 2024)
Tempe, a fermented soybean food rich in polyphenols including isoflavones, is valued for its health benefits, notably its antioxidants. Concerns about glyphosate residues in crops have led to increased demand for organic soy products, including tempe. The study aimed to investigate the metabolomic profiles of tempe and its bioactive potentials prior to and following in vitro simulated gastrointestinal digestion. Conventional soybean (CS), conventional tempe (CT), conventional tempe digesta (CTD), organic soybean (OS), organic tempe (OT) and organic tempe digesta (OTD) were analysed for various assays. The study observed a significant decrease in the total phenolic and flavonoid levels for conventional and organic samples in tempe extracts (CT, OT) compared to tempe digesta (CTD, OTD). Organic tempe digesta has a higher total phenolic content (CTD = 22.55 μg GAE/g, OTD = 41.36 μg GAE/g) and flavonoid content (CTD = 4.64 μg QE/g, OTD = 10.06 μg QE/g) compared to conventional tempe digesta. However, there is a significant difference in the bioaccessibility of phenolic (CT = 74.77 %, OT = 59.20 %) and flavonoid (CT = 49.4 %, OT = 57.52 %) in both organic and conventional tempe. Tempe consistently surpasses soybean in antioxidant assays such as DPPH, ABTS, and FRAP. Organic tempe digesta exhibits the most elevated levels of antioxidants. Using GNPS and the SIRIUS database, 34 metabolites were annotated according to the criteria of having a VIP score > 1.5, a log2(FC) > 1, and a p-value < 0.05. From the list, 26 metabolites demonstrated a positive correlation with antioxidant activity, DPPH, and FRAP. Molecular networking enables the visualization of 12 prominent isoflavones, namely daidzein, daidzin, genistein, genistin, glycitein, glycitin, 6″-O-malonyldaidzin, 6″-O-acetylgenistin, 6″-O-acetyldaidzin, and 7,8,4′- trihydroxyisoflavone. Interestingly, aglycone isoflavones are abundant in organic tempe digesta while glycoside isoflavones are abundant in organic and conventional soybeans. Overall, the findings indicate that tempe digesta exhibits distinct metabolic patterns and bioactive potentials.